2022
DOI: 10.1073/pnas.2122788119
|View full text |Cite
|
Sign up to set email alerts
|

LOCOM: A logistic regression model for testing differential abundance in compositional microbiome data with false discovery rate control

Abstract: Compositional analysis is based on the premise that a relatively small proportion of taxa are differentially abundant, while the ratios of the relative abundances of the remaining taxa remain unchanged. Most existing methods use log-transformed data, but log-transformation of data with pervasive zero counts is problematic, and these methods cannot always control the false discovery rate (FDR). Further, high-throughput microbiome data such as 16S amplicon or metagenomic sequencing are subject to experimental bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 48 publications
(92 reference statements)
0
37
0
Order By: Relevance
“…In this study, we found that LOCOM was robust to not only main effect biases but also a reasonable range of interaction biases. The other methods tended to have inflated FDR even when there were only main effect biases; many of them did not control the FDR even when there was no experimental bias at all (results shown in [2]). LOCOM maintained the 6 highest sensitivity among all methods even when the other methods did not control the FDR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we found that LOCOM was robust to not only main effect biases but also a reasonable range of interaction biases. The other methods tended to have inflated FDR even when there were only main effect biases; many of them did not control the FDR even when there was no experimental bias at all (results shown in [2]). LOCOM maintained the 6 highest sensitivity among all methods even when the other methods did not control the FDR.…”
Section: Discussionmentioning
confidence: 99%
“…We considered both binary and continuous traits of 4 interest without any confounding covariates; we also considered a binary confounder when the trait was binary. We used the two sets of causal taxa (i.e., taxa that are associated with the trait) that were used in [2], namely, a random sample of 20 taxa (referred to as M1) and the five most abundant taxa (M2); we assumed a common effect size β of the trait on all causal taxa.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some methods used in microbiome analysis, such as ALDEx2 [ 13 ], LinDA [ 39 , 40 ], ANCOM [ 26 ], ANCOM-BC [ 23 ], fastANCOM [ 39 ] and LOOCM [ 21 ], perform the log-ratio approach to identify differential abundant taxa between two study groups. Here we introduce coda4microbiome , a new R package for analyzing microbiome data within the CoDA framework in both, cross-sectional and longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%